Wokół Nas . no. 3, 1986 - Komitet Oporu Społecznego "Solidarność" (KOS, 1986)
Motto: "Only those liberated by their own will shall see the day of liberation" Stanisław Wyspiański, "Wyzwolenie" [Liberation]